IMPLEMENTASI BOOST CONVERTER PADA SISTEM SEL VOLTA BERBAHAN AIR LAUT DENGAN KATODA TEMBAGA BERLAPIS PERAK - Pauzi, Gurum Ahmad; Rianita Baiti; Supriyanto, Amir; Junaidi (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
The overpotential characteristics of a high-voltage seawater battery system were systematically analyzed, employing a silver-coated copper cathode and a zinc anode. This study evaluated the system's electrochemical performance using a quantitative approach based on the Butler-Volmer equation. The exchange current density and the time-dependent overpotential profile were estimated to gain insight into the electrochemical kinetics involved. A total of 20 voltaic cells were assembled in a series-parallel configuration and subjected to loaded operation for 55 minutes. During the experiment, an exponential decrease in current—from 2.6 mA to 0 mA—was recorded, which was attributed to internal resistance and charge transfer limitations. The modeling process was carried out using nonlinear fitting, through which the exchange current density was found to range between 0.15 and 0.3 mA/cm². The charge transfer coefficient (α) was also determined to be approximately 0.5, indicating a relatively balanced rate of anodic and cathodic reactions. It was demonstrated that the silver coating on the copper cathode significantly enhanced electrochemical activity by improving the catalytic surface, thereby increasing both current response and long-term system stability. These results highlight the potential of surface-modified electrodes in advancing seawater battery technologies.